Breath of Proximity: Intersubjectivity, Ethics and Peace - Škof, Lenart (Springer, 2015)
This book offers an original contribution towards a new theory of intersubjectivity which places ethics of breath, hospitality and non-violence in the forefront. Emphasizing Indian philosophy and religion (Vedas and Upanishads) and related cross-cultural interpretations, it provides new intercultural interpretations of key Western concepts which traditionally were developed and followed in the vein of re-conceptualizations or revitalizations of Greek thought, as in Nietzsche and Heidegger, for example. The significance of the book lies in its establishment of a new platform for thinking philosophically about intersubjectivity, so as to nudge contemporary philosophy towards a more sensitive approach, which is needed in our times. Its originality lies in its innovative approach, which searches for the origin of ethical gestures (represented in respecting the breath/breathing) through the newly introduced concept of “mesocosm” as a space of a ritual, or a new ethical space of intersubjective encounters. The book also introduces the possibility of an original ethics based on breath. Intended for philosophers, feminists and others concerned with intercultural philosophy and comparative religion, the book will appeal to readers interested in contemporary ethical and political theories of peaceful conflict resolution and concepts of hospitality. A Breath of Hospitality will benefit all who seek a more sensitive approach in philosophy, including philosophy of religion, and often-neglected practical and educational layers of our everyday intersubjective relations.